Structural Optimization of Inhibitors of α-Synuclein Fibril Growth: Affinity to the Fibril End as a Crucial Factor - Afitska, Kseniia; Priss, Anastasiia; Yushchenko, Dmytro A; Shvadchak, Volodymyr V (Journal of Molecular Biology, 2020)
BACKGROUND: Misfolding of the neuronal protein α-synuclein into amyloid fibrils is a pathological hallmark of Parkinson's disease, a neurodegenerative disorder that has no cure. Inhibition of the fibril growth is considered a promising therapeutic approach. However, the majority of the existing inhibitors are either unspecific or work at high micromolar concentrations. Earlier, we created a protein-based inhibitor of α-synuclein fibril growth that consists of an α-synuclein moiety and a bulky group. It specifically binds to α-synuclein fibril ends and blocks them by creating steric hindrance to subsequent monomer binding. RESULTS: In this work, we prepared a series of inhibitors with modified α-synuclein moieties and bulky groups of different structure, size, and position. We studied the structure-activity relationship of these inhibitors and optimized them by improving affinity to the fibril end and blocking efficiency. The inhibitors were tested in a Thioflavin T-based kinetic assay, and their affinity to the fibril ends was measured by fluorescence anisotropy. We showed that decrease in electrostatic repulsion between inhibitor and fibril end improved the inhibitor efficiency. Inhibitors with rigid β-sheet-rich bulky groups bind to fibril ends stronger than monomeric α-synuclein and therefore have a high inhibition efficiency, showing a linear correlation between Kd and IC50. SIGNIFICANCE: We determined which properties of inhibitor molecules are the most important for good performance and found that the inhibitor affinity to the fibril end is a key feature that determines its inhibition efficiency. Applying this knowledge, we improved existing inhibitors and reached IC50 value of 300 nM.
Keywords: vazba proteinů; fluorescenční polarizace; Fluorescence Polarization; lidé; Humans; proteinové agregáty; vztahy mezi strukturou a aktivitou; Protein Binding; benzothiazoly; Kinetics; Structure-Activity Relationship; alpha-Synuclein; amyloid; Benzothiazoles; alfa-synuklein; Protein Aggregates; Amyloid; kinetika